Influence of soil management for soybean production under microbial diversity in amazon soils - Cardenas-Alegria, Oscar Victor; Dantas, Carlos Willian Dias; Silva Guedes Lobato, Elaine Maria; Da Silva, Sandro Patroca; Moraes, Cássia de Sousa; Cruz, Ana Cecília Ribeiro; Ramos, Rommel Thiago Jucá; Carneiro, Adriana Ribeiro (Frontiers in Environmental Science, 2022)
The tropical Amazon has a unique biodiversity that has been affected by the development of pastures and economically important crops, such as soybeans. In the Amazon soil, the communities of microorganisms are diverse and act in different biogeochemical activities relevant to their adaptation to the environment. The assessment of changes in soil microorganism communities is essential to consider the impact of agribusiness action in one of the wealthiest regions in diversity in the world. Thus, the soil microbial diversity of the Amazon forest, the north region of Brazil, was evaluated regarding the influence of soybean farming with regions with periods of two and fourteen years of exploitation, with regions of pasture and forest area, through the metagenomic approach with new generation sequencing technology, in addition, it was considered chemical characteristics such as pH value, organic matter content, macronutrients, micronutrients, and cations. High microbial diversity was identified at all collection sites and, despite this, bacterial, archaeal, and virus communities were very diverse between sites, with higher identification of Enterobacter cloacae and species of Pseudomonas, Pseudoplusia includens, Methanosarcina barkeri in the farmed and pasture, whose microbial diversity is influenced by the presence of cations and the interaction of organic matter with clay. It was evident that there is a change in the communities of native microorganisms for others adapted in the areas that had their vegetal cover eliminated.